Ciclo anual de estratificación y circulación en el Embalse Arenal, Costa Rica - Umaña Villalobos, Gerardo (2006)
Yearly cycle of stratification and circulation at the Arenal Reservoir, Costa Rica. The behavior of the water column of Arenal Reservoir, a tropical reservoir in Costa Rica, is analyzed based on temperature and dissolved oxygen data gathered on a monthly to bimonthly basis between 1986 and 1992. The depth profiles of temperature at Arenal Reservoir show the typical asymmetry of reservoirs, with a greater stratification in its deeper part near the dam, even though the main outflow is located at its head at the northwest end instead of the dam. A comparison of sampling stations at both ends show a deeper circulation pattern at the northern end. This coincides with other reports of a tilted structure of the thermal isopleth pattern in front of the water outlet. The dissolved oxygen showed some degree of anoxia at the bottom during part of the year, mainly from May until October. This was caused by the decomposition of the organic matter accumulated at the bottom at the time, mainly as remains of the vegetation from the former lagoon that was not removed before flooding. The stratification is clearly seasonal, occurring during the rainy season (April to October), specially in the deeper zones of the reservoir. Rev. Biol. Trop. 54 (Suppl. 1): 257-263. Epub 2006 Sept. 30.